Model-based detection of sensor faults under changing temperature conditions. (March 2014) - Buethe, Inka; Eckstein, Benjamin; Fritzen, Claus-Peter
Nowadays, a variety of civil, aeronautic or mechanical engineering structures need regular inspections. While non-destructive testing has become state of the art, there is a trend towards online testing on demand using built-in sensors. A vast amount of in-service monitoring, as part of structural health monitoring, uses piezoelectric elements. Their deployment requires a control of the sensor performance in order to prevent false alarm. Several kinds of damage can influence the sensor performance, for example, degradation of piezoceramic or adhesive, debonding or breakage of the element. Therefore, this paper aims to detect damage of circular piezoelectric elements and their bonding layers during in-service monitoring. For this purpose, a local method, using the coupled electro-mechanical admittance, is proposed. However, changing environmental and operational conditions such as temperature have an effect on the measured quantities, masking the damage. To cope with this, the dynamic behaviour of an attached piezoelectric element including temperature trends is modelled to enable physics-based temperature compensation. This novel combination of an improved analytical model, updated according to impedance measurements, realizes a method less dependent on experimental baseline data, than the sole comparison of experimental data, established in many monitoring systems. By comparison with experimentally obtained electro-mechanical susceptance the physical model of circular piezoelectric elements is validated. The feasibility of the proposed method is presented employing experimental data of piezoelectric elements mounted on aluminium coupons, partly damaged with degradation and sensor breakage. The application produces promising results, detecting the created defects.